Fock space approach to schnakenberg model - LEANDRO, Marlon Oliveira Martins (2016)
This work has as objective to study the relationship between Fock spaces, quantum operators and chemical reaction systems used to model many stochastic processes with biological motivation, such as population growth, heartbeats and cell metabolism. In particular, we work with a generalization of Schnakenberg model, in its deterministic and stochastic versions, and which is used to describe the process of cellular glycolysis. As it is a new and at the same time a interdisciplinary area, involving knowledge in stochastic processes, theoretical physics, chemistry and biomathematics, this text seeks to be self-contained, including all the elements needed for the study of theme, for the purpose of contribute to the better understanding between these diverse areas.